Features of myocardial damage at COVID-19 - S. H. Hamidov; A. G. Obrezan; P. S. Lobanova; S. V. Azarenko (Евразийский Кардиологический Журнал, 2022)
This work is devoted to a literature review of published articles, where studies are focused on studying the frequency, structure of complications of cardiovascular diseases in patients with COVID-19, that occurred in vivo and post-mortem: myocarditis, myocardial damage, AMI, and other thrombotic events. Some studies also provide comparative data on COVID-19+ and COVID-19- patients, complication patterns, and mortality rates. The results of the studied materials shows that, the frequency of cardiac complications and the number of deaths are significantly more common in patients with concomitant diseases such as arterial hypertension, diabetes mellitus, obesity, CKD, arrhythmias. Patients over 60 years of age are at increased risk of a severe course of the disease, this is due to the fact that these individuals have concomitant chronic diseases that are decompensated due to an acute infectious process, reducing the adaptive capabilities of the organism, and lead to a deterioration in survival rates.